Continuous implementation of irrigation operations by water pumps in semi-arid regions (MMIT Proceedings, 2025)
This article provides an in-depth analysis of the efficient use of water resources in Uzbekistan’s agriculture and irrigation systems. It examines issues related to water scarcity in regional irrigation networks, the environmental impact of saline waters, and their treatment processes. In particular, the article discusses new technologies for improving water pumping systems, recycling, and efficient management of water resources, including methods such as reverse osmosis and electrodialysis. The research offers practical recommendations for improving melioration conditions, enhancing economic efficiency, and ensuring the optimal use of natural resources. Overall, this scientific work is dedicated to studying and improving water management strategies in agriculture and irrigation systems